Disturbance-free digital holographic microscopy via a micro-phase-step approach. (May 2015) - Chang, Chi-Ching; Shiu, Ming-Tzung; Wang, Je-Chung; Wu, Chia-Hao; Chew, Yang-Kun
Abstract: This work proposes a cost-effective, simple, micro-phase-step (MPS) method for suppressing the zero-order diffraction and conjugate-image interferences that are caused during digital holographic microscopic image reconstruction. The proposed MPS method replaces the conventional phase modulation approach; it uses a rotatable cover glass that enables smooth modification of the incidence angle and the optical path of the reference beam. This setup allows the phase step to be accurately estimated by shifting the reference wave phase more freely close to π /2, at which the background noise can be suppressed more effectively. In the proposed MPS method, the optimal conditions for suppressing conjugate-image interference are identified using a relatively moderate intensity distribution and suppression of noise in the numerically reconstructed object wave-field. In addition, the proposed method mitigates the effect of disturbances that are caused by environmental factors, such as minor vibrations and small changes in temperature and humidity. Importantly, only two holograms are required to satisfy the objective of image reconstruction. The results in this work reveal that even with intentional interference caused by minor vibrations, conjugate-image interference can still be suppressed by determining the phase deviation between the two original holograms. Highlight: Rather than the expensive PZT, a microscope cover glass as phase modulator is able to modulate the reference wave phase accurately and smoothly. Only two holograms are needed for image reconstruction, reducing the disturbances that are caused by environmental factors. With simple numerical calculation, even under intentionally created disturbances by minor vibrations, conjugate image interference can still be suppressed as long as the phase deviation between the two original holograms is identified.